2023
DOI: 10.1371/journal.pone.0280285
|View full text |Cite
|
Sign up to set email alerts
|

Populist ideology, ideological attitudes, and anti-immigration attitudes as an integrated system of beliefs

Abstract: A challenge for the identification of the core components of a beliefs system is the topological examination of these components within the overall structure of the said system. By modeling beliefs as nodes of interconnected networks, this research investigated the centrality of adherence to populist ideology and classical ideological attitudes in relation to voting behavior and negative feelings toward immigrants. Data from a sample of 774 Italian adults were examined by means of three Network Analysis models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Populism, defined by the ideational approach, comprises three core components: opposition to elites, people's sovereignty, and a Manichean worldview (Mudde, 2004(Mudde, , 2017Hawkins and Kaltwasser, 2018). In contrast to group-based dominance ideologies, including SDO, which emphasize preserving social hierarchies, populist ideology leans toward "flattening hierarchies" (Pellegrini, 2023). Unlike SDO, which categorizes society into inferior and superior groups (Pratto et al, 1994), populist ideology views all "ordinary people" as a homogeneous entity, with the elite seen as the adversary (e.g., Hawkins and Kaltwasser, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Populism, defined by the ideational approach, comprises three core components: opposition to elites, people's sovereignty, and a Manichean worldview (Mudde, 2004(Mudde, , 2017Hawkins and Kaltwasser, 2018). In contrast to group-based dominance ideologies, including SDO, which emphasize preserving social hierarchies, populist ideology leans toward "flattening hierarchies" (Pellegrini, 2023). Unlike SDO, which categorizes society into inferior and superior groups (Pratto et al, 1994), populist ideology views all "ordinary people" as a homogeneous entity, with the elite seen as the adversary (e.g., Hawkins and Kaltwasser, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research has found anti-immigrant sentiment is associated with being on the political right (Chandler and Tsai 2001;Lahav and Courtemanche 2012;Pellegrini 2023).…”
mentioning
confidence: 99%